Calcific Periarthritis as the Only Clinical Manifestation of Hypophosphatasia in Middle‐Aged Sisters. (April 2014) - Guañabens, Núria; Mumm, Steven; Möller, Ingrid; González‐Roca, Eva; Peris, Pilar; Demertzis, Jennifer L; Whyte, Michael P
ABSTRACT Hypophosphatasia (HPP) is the inborn error of metabolism that features low serum alkaline phosphatase (ALP) activity caused by loss‐of‐function mutation(s) within the gene for the tissue nonspecific isoenzyme of ALP (TNSALP). In HPP, extracellular accumulation of inorganic pyrophosphate (PPi), a TNSALP substrate and inhibitor of mineralization, leads frequently to premature tooth loss and often to rickets or osteomalacia. In affected adults, the excess PPi sometimes also causes calcium pyrophosphate dihydrate (CPPD) deposition, PPi arthropathy, or pseudogout, or seemingly paradoxical deposition of hydroxyapatite crystals in ligaments or around joints when the condition is called calcific periarthritis (CP). We report three middle‐aged sisters with CP as the only clinical manifestation of HPP. Each presented during early adult life with recurrent episodes of pain principally around the shoulders, elbows, wrists, hips, or Achilles tendon. Otherwise, they were in good health, including no history of unusual dental disease, fractures, or pseudofractures. Calcific deposits were identified in symptomatic areas principally by ultrasonographic assessment but also confirmed radiographically. All three sisters had low serum levels of total and bone‐specific ALP, hyperphosphatemia, and increased serum concentrations of the TNSALP substrate pyridoxal 5′‐phosphate together characteristic of HPP. Mutation analysis revealed that each carried a single unique 18‐bp duplication within TNSALP (c.188_205dup18, p.Gly63_Thr68dup) as did two of their healthy sons and their mother, who was without signs of CPPD deposition or CP but had knee osteoarthritis. We find that CP can be the only complication of HPP in adults. Thus, multiple juxta‐articular deposits of hydroxyapatite causing CP may be a useful sign of HPP, especially when the CP is familial. © 2014 American Society for Bone and Mineral Research.